Engaging Vocational High Students in Directed Reading Thinking Activity Strategy (Drta) Reading Comprehension in News Item Text - Prasetyo, Andrian Hadi; Ahmad, Yousef Bani (FKIP - Universitas Riau, 2025)
The phenomenon of Vocational High Students struggling with English reading comprehension, especially in news item text is considerably urgent, the level of English literacy among students’ is quite alarming. Many students could not understand what they read. The purpose of this research is to investigate the efficacy of the DRTA (Directed Reading Thinking Activity) strategy in engaging and improving vocational students’ comprehension and participation regarding news item texts. This research conducted in Qualitative research with a classroom action research (CAR) design. The data are collected from teacher’s reflective journals, students’ interviews, and class documents. The findings indicate that the application of the DRTA method enables students to engage through the cycles of prediction, verification, and reflection, evolve from passive to active readers. This method also improves students' cognitive, affective, and social engagement. The integration of DRTA with a genre-based approach (TLC-DG) further enhances students’ comprehension of the social structure and functions of texts. This evidence suggests the need to adopt DRTA as a pivotal approach to critical literacy in 21st century vocational education.